Design of Nuclear Installations Against External Events Excluding Earthquakes. - IAEA (IAEA, 2021)
"This Safety Guide provides recommendations on the design of nuclear installations for protection against the effects of external events (excluding earthquakes), meeting the applicable safety requirements established in relation to the design aspects of nuclear installations subjected to external events. It provides methods and procedures for defining an appropriate design for a nuclear installation, based on the site hazard evaluation and the layout of the installation. The aim is to provide design guidance, in particular for the protection of structures, systems and components important to safety against design basis external events. The guide also provides recommendations on the selection of beyond design basis external events, in order to check and verify safety margins."--Publisher's description.
Keywords: Nuclear facilities.; elektronické knihy; electronic books